Correlation between Interactive Multimedia-Based Suggestopedia and Vocabulary Mastery of Beginner Arabic Learners - Hizza, Afiqotul; Kholiq, Ilham Nur (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to analyze the relationship between the application of the Suggestopedia method based on interactive multimedia and vocabulary mastery (mufradat) among beginner Arabic language learners. This research uses a quantitative, correlational design. The research population consists of 10th-grade students at MAN 3 Banyuwangi for the 2025/2026 academic year, with a sample of 40 respondents selected through a cluster sampling technique. The research data consists of quantitative data obtained from 40 respondents. The data source was a questionnaire that measured multimedia usage and Arabic vocabulary mastery. Data collection was conducted using a Likert-scale questionnaire that has undergone validity and reliability testing. Data analysis used the Spearman Rank test, which was chosen because it is suitable for analyzing ordinal data or data that does not meet parametric assumptions and does not require normality. The research results show a strong and significant positive correlation between the application of interactive multimedia-based Suggestopedia and students' vocabulary mastery (r = 0.791; p < 0.05). These findings indicate that optimizing the application of this method contributes to improved vocabulary mastery. This research provides theoretical contributions and practical implications for the development of technology-based Arabic language-learning strategies for beginners.